The Impact of Ownership Structure on CSR Disclosure: Evidence from Indonesia - Peni Nugraheni; Arum Indrasari; Noradiva Hamzah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: When stakeholders want to invest in a company, CSR is one of the concerns. Thus, this study aims to examine the effect of ownership structure on corporate social responsibility disclosure in Indonesian companies. The ownership structure in this study consisted of managerial ownership, institutional ownership, public ownership, and foreign ownership.Design/Methodology/Approach: The samples in this study were companies listed on the Indonesian stock exchange from 2017 to 2019 that belonged to the sensitive industry category. The ownership structure comprised managerial ownership, institutional ownership, public ownership, and foreign ownership. CSR disclosure was measured using the Global Reporting Initiative (GRI). The data were then analyzed using panel data regression.Research findings: The results showed that institutional ownership positively affected CSR disclosure, while managerial, foreign, and public ownership did not affect CSR disclosure. Theoretical contribution/Originality: The company’s organs, including ownership structure, are expected to encourage companies to be more active in conducting CSR and disclosing it in company reports. However, while many ownership structures do not affect CSR, stakeholders and regulators need to encourage other instruments that can be used to increase CSR disclosure.